A Review of Developing Communication Skills for Students with Intellectual and Developmental Disabilities on College Campuses. Issue 2 (March 2021) - Pennington, Robert C.; Bross, Leslie Ann; Mazzotti, Valerie L.; Spooner, Fred; Harris, Ryan
In the current investigation, we reviewed the literature on communication interventions for individuals with intellectual and developmental disabilities (IDD) on college campuses. Eight studies met our inclusion criteria. Data were extracted related to participant demographics (e.g., disability, response form, type of postsecondary program) and study variables (e.g., design, settings, intervention). We evaluated the methodological quality of each study using the National Technical Assistance Center on Transition's Quality Indicator Checklist for single-case design studies. Results indicated a dearth of literature in this critical area and that extant literature reflected a primary research emphasis on the use of multi-component packages to teach communication skills to students with mild or no intellectual disability. Limitations and implications for research and practice for transition professionals and university campus providers are discussed.